Usurpaciones en Britania (406-407): hipótesis sobre sus causas y protagonistas - Sanz Huesma, Francisco Javier (Gerión. Revista de Historia Antigua, 2005)
In this article I support three hypothesises. First is that Marcus, the first Briton usurper, was “comes Britanniarum”. Secondly, the cause of the revolt was not the pressure of barbarian people in the island (it was not less in the forth century) but a lack of payement to the garrison placed in.This garrison included not only static troops, but also comitatenses. Finally, the third hypotesis refers to Constantinus, the future Constantinus III. He was not an occasional usurper appointed by troops, but an skilled politician who designed his strategy from the beginning: he named Gratian and then he removed him from power in order to take it upon himself.